KKN Tematik Universitas Muhammadiyah Enrekang: Pelaksanaan Kegiatan Mahasiswa KKNT Di Desa Bungin Kecamatan Bungin - Ganti, Rahmawati; Gustiani, Lisa; Jumra, Jumra; Wahyula, Ilda Asti; Wahyuni, Sri; Jupri, Eka Safitri; Hajrah, Nur; Zakinah, Siti; Wiwik, Wiwik; Sledi, Egi; Abbas, Basrul; Arsil, Arsil; Asri, Riska Binti; Amin, Ahmad; Atika, Siti Nur; Rahmawati, Rahmawati; Suryani, Aisyah; Muchtar, Achmad Dahlan; Elihami, Elihami (MASPUL JOURNAL OF COMMUNITY EMPOWERMENT, 2023)
Thematic KKN at Muhammadiyah University Enrekang in Bungin village, Bungin sub-district, Enrekang Regency is a form of community service activity. Real Work Lectures will be held from 01 September 2023 to 02 December 2023. Activities consist of core activities and additional activities. KKN activities aim to provide experience and as a learning process for students to explore village potentials that can be developed by the community. The method for implementing KKN at the location consists of survey activities, implementation of core activities and additional activities. Additional KKN student activities receive support from the local government and village community. This is shown in many KKN student activities involving people from various groups. The village government involves many KKN students in implementing activities such as elderly exercise, Posyandu activities and stunting awareness. Other forms of activities involve teenagers and school children at elementary, middle and high school levels, such as accompanying and teaching the Koran, morning exercise and scout activities, numeracy and literacy activities, attitude product activities, hydroponic system plant cultivation activities, and competition activities. It is hoped that the Enrekang Muhammadiyah University KKN activities will provide benefits to the village community